2006
DOI: 10.1182/blood-2005-05-1922
|View full text |Cite
|
Sign up to set email alerts
|

Human embryonic stem cell–derived hematopoietic cells are capable of engrafting primary as well as secondary fetal sheep recipients

Abstract: The human/sheep xenograft model has proven valuable in assessing the in vivo hematopoietic activity of stem cells from a variety of fetal and postnatal human sources. CD34 ؉ /lineage ؊ or CD34 ؉ /CD38 ؊ cells isolated from human embryonic stem cells (hESCs) differentiated on S17 feeder layer were transplanted by intraperitoneal injections into fetal sheep. Chimerism in primary transplants was established with polymerase chain reaction (PCR) and flow cytometry of bone marrow and peripheral blood samples. Whole … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
71
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(77 citation statements)
references
References 18 publications
5
71
0
1
Order By: Relevance
“…The repopulating capacity of these progenitors does increase with time in vivo and in P-Sp explants in vitro (Medvinsky and Dzierzak, 1996;Taoudi et al, 2008), suggesting that additional maturation steps are required to promote the differentiation of these pre-HSC progenitors to functional HSCs (Medvinsky and Dzierzak, 1996;Taoudi et al, 2008). Studies with human ESCs have indicated that interactions with appropriate stromal cell lines in vitro might provide the appropriate maturation signals required for the generation of HSCs (Ledran et al, 2008;Narayan et al, 2006;Wang et al, 2005a). Although the development of long-term repopulating multipotent HSCs under these conditions remains to be demonstrated, these findings do 2837 RESEARCH ARTICLE Stem cell-derived hematopoiesis highlight the potential importance of interactions with the appropriate niche/cellular microenvironment for the differentiation and maturation of HSCs from PSCs.…”
Section: Research Articlementioning
confidence: 99%
“…The repopulating capacity of these progenitors does increase with time in vivo and in P-Sp explants in vitro (Medvinsky and Dzierzak, 1996;Taoudi et al, 2008), suggesting that additional maturation steps are required to promote the differentiation of these pre-HSC progenitors to functional HSCs (Medvinsky and Dzierzak, 1996;Taoudi et al, 2008). Studies with human ESCs have indicated that interactions with appropriate stromal cell lines in vitro might provide the appropriate maturation signals required for the generation of HSCs (Ledran et al, 2008;Narayan et al, 2006;Wang et al, 2005a). Although the development of long-term repopulating multipotent HSCs under these conditions remains to be demonstrated, these findings do 2837 RESEARCH ARTICLE Stem cell-derived hematopoiesis highlight the potential importance of interactions with the appropriate niche/cellular microenvironment for the differentiation and maturation of HSCs from PSCs.…”
Section: Research Articlementioning
confidence: 99%
“…At present, multipotent hematopoietic progenitors (short-term HSC) with limited engrafting ability in transplanted mice were obtained (Woods et al, 2011). Other groups reported efficient generation of cells that mostly produce the myeloid lineage following long term engraftment or produce CD34+ hematopoietic precursors that have phenotype similar to adult HSC but might best correspond to the embryonic stage of yolk-sac, aortogonadalmesonephros (AGM), and/or fetal liver stage of hematopoiesis (Melichar et al, 2011;Narayan et al, 2006 andfor review : Tian andKaufman, 2008). More recently, the polycomb group protein Bmi1 was shown to promote more than 100-fold increase of hematopoietic cell development from ESC (Ding et al, 2011).…”
Section: Obtaining Hsc From Escmentioning
confidence: 99%
“…[2][3][4][5] Strikingly, these patients are late-onset clinical phenocopies of patients with Mendelian susceptibility to mycobacterial disease (MSMD) carrying inborn errors of IFN-␥ immunity. 6 This observation alone strongly suggested that autoantibodies against IFN-␥ were the cause rather than a…”
mentioning
confidence: 99%
“…While several studies examine transplantation of human ESC or iPSCderived hematopoietic cells into immunodeficient mice or fetal sheep models, the overall level of engraftment is typically low and primarily consists of myeloid cells. [4][5][6] In addition, while strategies such as overexpression of HoxB4 in mouse ESCs leads to development of transplantable hematopoietic stem cells, HOXB4 does not have the same effect when expressed in human ESCs. 4 Here, Amabile and colleagues more closely examine the hematopoietic potential of teratomas produced from human iPSCs that are grown subcutaneously and intramuscularly in immunodeficient NOD/SCID/IL2R␥c Ϫ/Ϫ (NSG) mice (see figure).…”
mentioning
confidence: 99%